GRUP – Γ DUAL DARI SUATU GRUP–Γ - Sumanto, Y.D (MATEMATIKA, 2012)
On  of   can be considered as binary operation on . If there are  such that  is a group, then for any ,  is also a group and S  called as   . Otherwise for every element of  can be considered as binary operation on   . There are  such that  is - group and every is a group, troughout in this paper  is called  as dual group from